South Asia Economic Focus, June 2012: Creating Fiscal Space through Revenue Mobilization - World Bank (Washington, DC, 2012)
This book focuses on the creation of fiscal space through revenue mobilization, although such efforts are best made using a comprehensive framework that examines all available sources. Those sources include: (a) reducing lower-priority spending, (b) enhancing the capacity to implement priorities so that capital investment and social service provision can be carried out at reduced cost, (c) reforming subsidies or transfer programs to make them more targeted and efficient, and (d) rationalizing administered prices of publicly provided goods and services. The book is organized as follows: chapter two examines the factors that could account for the low revenue collection in South Asia. Chapter three describes the tax systems in South Asia and assesses them against a number of benchmarks that are commonly used in the literature, such as international comparisons, estimates of buoyancy, and tax yields, and then discusses key elements of tax administration in South Asia. Chapter four presents information on nontax revenues, and chapter five concludes with some key policy implications.